Analisis Pengaruh Kinerja Karyawan Dan Kualitas Pelayanan Terhadap Loyalitas Pelanggan Pada Pt. Azure Samudera Karsa - Labella, Intan Freshia (Institut Transportasi dan Logistik Trisakti, 2024)
PT. Azure Samudera Karsa is a company engaged in the marine sector that focuses on ship surveys (Marine inspection/survey) & seafarer certificates (Marine ceritifcation services) & Procurement of Goods (Provision Supply). The purpose of this study was to determine and analyze the influence of employee performance and service quality on customer loyalty at PT. Azure Samudera Karsa. The method used in this study is a quantitative method, involving 84 respondents using a sampling technique with the Slovin formula and using a questionnaire (Likert scale) and library research. And hypothesis testing using SPSS version 23. Data analysis used descriptive statistical tests, data instrument tests (validity tests and reliability tests), classical hypothesis tests including normality tests, multicollinearity tests, heteroscedasticity, multiple linear regression analysis, coefficient of determination and hypothesis tests (partial tests or t tests and F tests). The results of the regression analysis showed that employee performance and service quality variables had a positive and significant effect on customer loyalty. The results of the t test showed that employee performance and service quality had a significant partial effect on customer loyalty. Based on the results of the F test, it was found that employee performance and service quality simultaneously have a significant effect on customer loyalty.